Manajemen Handover Metode SBAR (Situation, Background, Assessment, Recommendation) dalam Meningkatkan Komunikasi Efektif - Gilang Rahmatulloh; Krisna Yetti; Dyah Fitri Wulandari; Ahsan Ahsan (Journal of Telenursing (JOTING), 2022)
This study aims to analyze the application of the SBAR method of handover management innovation in improving effective communication. The method used is a case study that starts from the process of identification, analysis, problem priority setting, plan of action (POA), implementation and evaluation. Data collection was done by interview, observation and survey methods. The results of the priority problems were analyzed using fishbone analysis. The results showed that the SBAR method of handover management innovation influenced the team leader's ability to carry out handovers. The evaluation results show that 75% of the team leaders can properly fill out handover forms and submit handovers using the SBAR method. In conclusion, the SBAR method of handover management innovation can be used to improve handover capabilities to improve effective communication. Keywords: Handover, Effective communication, Patient safety, SBAR